Nursing Interventions for Preventing Hospital-Acquired Infections - Alnadawy, Ohood Hameed; Albogami, Norah Fahad; Alfahmi, Maram Saed Saad; Haqwi, Nada Mohammed; Takroni, Amna Ahmedoh Eissa; Dowaid, Ebtisam Ali Ahmead (International Journal of Scientific Research and Management (IJSRM), 2024)
Hospital-acquired infections (HAIs) are a significant contributor to patient morbidity, mortality, and healthcare costs. With an increasing emphasis on patient safety and infection control, nursing interventions play a vital role in reducing the incidence of HAIs. This systematic review and meta-analysis evaluated the effectiveness of nursing-led interventions in preventing HAIs, focusing on four primary strategies: hand hygiene, aseptic technique, environmental cleaning, and patient education. A total of 52 peer-reviewed studies, including over 50,000 patient cases across various healthcare settings, were analyzed. The meta-analysis revealed that hand hygiene adherence led to a 35% reduction in HAIs, with an odds ratio (OR) of 0.65 (95% CI: 0.54–0.79). Structured training in aseptic techniques for invasive procedures correlated with a 40% reduction in catheter-associated infections (OR: 0.60, 95% CI: 0.50–0.75), while enhanced environmental cleaning protocols decreased HAI rates by 30% (OR: 0.70, 95% CI: 0.55–0.89). Patient education showed a 15% reduction in HAIs, although results were less statistically significant. These findings highlight the essential role of nursing interventions in infection control and underscore the need for continuous training, compliance monitoring, and institutional support. Future research should explore integrated infection prevention programs and technological innovations to improve adherence and expand patient education initiatives. Overall, nursing interventions remain crucial to achieving lower HAI rates and enhancing patient safety.